Impact of learners' perceptions of a high-stakes test on their learning motivation and learning time allotment: A study on the washback mechanism. Issue 12 (December 2022) - Dong, Manxia; Liu, Xiaohua
Abstract: This study investigates the relationships between learners' perceptions of a high-stakes test and their learning motivations and time allotment to explore the mechanism of test washback on learning. A questionnaire was administered to 3105 Chinese senior high school students. Descriptive statistics, exploratory factor analysis, standard multiple regression and structural equation modelling were performed. The study found that students' positive test perceptions (i.e., validity and importance) better predicted their intrinsic motivations (i.e., communicative and development motivations) than their negative test perceptions (i.e., perceptions of test impact), which were found to better predict their extrinsic motivation towards external requirements. In addition, students' perceptions of test validity and test impact both had direct effects on learning time allotment and a small indirect effect through development motivation and requirement motivation, while perceptions of test importance only indirectly influenced learning time allotment through development motivation. These findings have important implications for learning and teaching. Abstract : Washback mechanism; Test perceptions; Learning motivation; Learning time allotment